Flowability Properties of PLA/PA12 Composite with Varying Wollastonite Concentrations for 3D Printing Applications - Mustaza, Nur Munirah; Mohd Salleh, Farrahshaida; Abdullah, Abdul Manaf; Ramli, Mohd Ikram; Tharazi, Izdihar; Ismail, Muhammad Hussain (International Journal of Integrated Engineering, 2025)
This study evaluates the rheological properties and flow behaviour of PLA/PA12 composites with varying concentrations of wollastonite (WA) ceramic particles (5, 10, and 15 wt.%) to enhance their biological performance and printability in 3D printing applications. Achieving the right balance of viscosity and flow is crucial for producing high-quality filaments and reliable 3D printed structures. Comprehensive rheological analysis and material characterization were conducted, including particle size distribution, SEM, and EDX. The flow behaviour index (n) was calculated, and physical observations of extruded materials were assessed for surface quality and dimensional consistency. The 10 wt.% WA composite consistently demonstrated superior rheological properties, exhibiting optimal pseudoplastic behavior with an n value range of 0.073–0.439 and a viscosity of 5919 Pa·s at 140?°C, which was the lowest among the composites tested, ensuring smooth extrusion and structural integrity. SEM analysis showed a uniform microstructure with well-dispersed WA particles in the 10 wt.% WA composite, while the 5 wt.% WA and 15 wt.% WA composites displayed suboptimal particle distribution. Physical observations confirmed that the 10 wt.% WA composite produced a smooth, consistent extrudate, essential for high-quality filament fabrication and reliable 3D printing. These findings highlight the 10 wt.% WA composite as the most promising candidate for efficient and effective 3D printing.